Industry And Academic Collaboration In English Language Learning According To The Latest Curriculum - Fibria Cahyani; Dyah Nugraheny Priastuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The transformation of higher education in Indonesia encourages study programs, including English Education at IKIP Widya Darma, to strengthen collaboration between academia and industry. This article discusses the important role of this synergy in learning English that is relevant to the needs of the world of work and the latest curriculum developments, especially the Merdeka Curriculum. This collaboration includes aligning learning outcomes with industry competencies, involving practitioners as guest lecturers, internship programs, and developing work-based teaching materials. Through this approach, students not only master linguistic theory and pedagogy, but also communication skills, critical thinking, and readiness to face global challenges. The study also identified some good practices at IKIP Widya Darma as well as challenges in building sustainable collaboration. The results of the analysis show that industry-academic collaboration contributes significantly to improving the quality of graduates and the relevance of English learning to the professional world.